Bank depth, stock market liquidity and urbanisation at various stages of economic development and time period: a simultaneous equations approach - Jin, Xiaoxue (2017)
The finance and growth nexus has been discussed since the last century. Elements related to them also attract a lot of attentions in the research area. This study explores the systematic interaction among bank depth, stock market liquidity, and urbanisation. By constructing a Simultaneous Equations Model (SEM) consists of three equations, cross-equations correlations were taken into account in the Three-stage Least Squared (3SLS) estimation model using a large and new panel dataset of 43 economies for the time period 1990 to 2014. In the meantime, multidimensional analysis was conducted by splitting the sample into different groups to study the difference among countries in various stages of economic development and time period. Positive and significant impact is found from bank depth to stock market liquidity while mutual positive effect exists between urbanisation and bank depth. The stock market liquidity impact urbanisation positively but such impact is not significant. However, since both bank depth and stock market liquidity both positively predict urbanisation when entered together in the regression, the results are consistent with the views that financial development provides important services to growth, in this case, the growth of urbanisation. Limitations and further research are suggested in the last.